Financial literacy, behavior and vulnerability among Malaysian households: does gender matter? - Sabri, Mohamad Fazli; Cheng, Eugene Xi Aw; Abdul Rahim @ Abdul Wahab, Husniyah; Burhan, Nik Ahmad Sufian; Othman, Mohd Amim; Simanjuntak, Megawati (Universiti Putra Malaysia, 2021)
This study aims to identify the factors determining financial vulnerability among Malaysia households. A questionnaire-based survey was conducted using multi-stage sampling technique. In total, 578 useable responses were collected and data were analyzed using partial least square structural equation modeling. The empirical results revealed that i) financial literacy positively influenced financial behavior, ii) financial behavior negatively influenced financial vulnerability, iii) financial behavior mediates the relationship between financial literacy and financial vulnerability, iv) gender moderates the relationship between financial behavior and financial vulnerability. This study enriches the theoretical foundations of financial vulnerability through the exploration of mediation and moderation mechanism. Implications and future research suggestions are discussed.